COVID-19 Prevalence and Mortality Among Schizophrenia Patients: A Large-Scale Retrospective Cohort Study. (19th February 2021) - Tzur Bitan, Dana; Krieger, Israel; Kridin, Khalaf; Komantscher, Doron; Scheinman, Yochai; Weinstein, Orly; Cohen, Arnon Dov; Cicurel, Assi Albert; Feingold, Daniel
Abstract: Objective: Individuals with schizophrenia may be at an increased risk for COVID-19 morbidity due to the disease characteristics. In this study, we aimed to explore the odds of significant COVID-19 morbidity and mortality among schizophrenia patients while controlling for potential sociodemographic and medical confounders. Methods: Schizophrenia patients and age-and-sex matched controls (total n = 51 078) were assessed for frequency of COVID-19 positivity, hospitalizations, and mortality. The odds for COVID-19-associated hospitalization and mortality were calculated using logistic regression models, while controlling for age, sex, marital status, sector, socioeconomic status, diabetes, ischemic heart disease, hypertension, hyperlipidemia, obesity, smoking, and chronic obstructive pulmonary disease. Results: Individuals with schizophrenia were less likely to test positive for COVID-19; however, they were twice as likely to be hospitalized for COVID-19 (OR 2.15 95% CI 1.63–2.82, P < .0001), even after controlling for sociodemographic and clinical risk factors (OR 1.88 95% CI 1.39–2.55, P < .0001). Furthermore, they were 3 times more likely to experience COVID-19 mortality (OR 3.27 95% CI 1.39–7.68, P < .0001), compared to controls. Conclusions: We found evidence of associations between schizophrenia and increased COVID-19 morbidity and mortality compared to controls regardless of sociodemographic and medical factors. As these patients present with a combination of potential risk factors for mortality, efforts should be made to minimize the effects of the pandemic on this vulnerable population.